2005
DOI: 10.1111/j.1365-2141.2005.05735.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age and gender on biology, clinical features and treatment outcome of non‐Hodgkin lymphoma in childhood and adolescence

Abstract: Summary We analysed the impact of age and gender on biology and outcome of 2084 patients diagnosed with non‐Hodgkin lymphoma (NHL) between October 1986 and December 2002 and treated according to the Berlin‐Frankfurt‐Münster (BFM) multicentre protocols NHL‐BFM‐86, ‐90 and ‐95. Median age at diagnosis was 8·0 years for 97 precursor B‐lymphoblastic lymphoma (pB‐LBL) patients, 8·8 years for 335 T‐lymphoblastic lymphoma (T‐LBL) patients, 8·4 years for 1004 Burkitt's lymphoma/leukaemia (BL/B‐AL) patients, 11·4 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
218
8
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(269 citation statements)
references
References 43 publications
35
218
8
8
Order By: Relevance
“…similar to several studies reported that lymphomas constitute about 10-12% of all malignancies in pediatric patients (Birch and Alston, 2003;Chiu and Weisenburger, 2003;Heerema et al, 2005). About 7-10% are nonHodgkin lymphomas (NHLs), and 4-7% are Hodgkin lymphomas (HLs) (Clarke and Glaser, 2002;Birch and Alston, 2003;Burkhardt et al, 2005).…”
Section: Discussionmentioning
confidence: 58%
“…similar to several studies reported that lymphomas constitute about 10-12% of all malignancies in pediatric patients (Birch and Alston, 2003;Chiu and Weisenburger, 2003;Heerema et al, 2005). About 7-10% are nonHodgkin lymphomas (NHLs), and 4-7% are Hodgkin lymphomas (HLs) (Clarke and Glaser, 2002;Birch and Alston, 2003;Burkhardt et al, 2005).…”
Section: Discussionmentioning
confidence: 58%
“…BL was the most common NHL subtype (69%) in our series. Furthermore, BL accounted for 78.2, 77.2, 68, 48.2, 42.2 and 39% of the cases in studies conducted in Brazil, Kuwait, Saudi Arabia, Germany, UK and Egypt, respectively (16,(21)(22)(23)(24)(25). By contrast, BL was encountered at a surprisingly low frequency (9-12%) in India, Pakistan and Shanghai (21,26).…”
Section: Discussionmentioning
confidence: 99%
“…23 Patients with pB-LBL were younger than those with T-LBL, as reported by others. 15,24 However, the median age at diagnosis for our patients with T-LBL was a little higher than reported before (around 8.8 years old). 24 As also reported in previous studies, there was a clear predominance of males (2:1).…”
Section: Discussionmentioning
confidence: 40%
“…The worst outcome of girls compared with boys observed only in patients older than 9 years has given rise to the hypothesis that advanced pubertal changes in girls compared with boys might contribute to inferior treatment results for females with increasing age. 24 In general, the outcome is inferior for CNS positive as compared with CNS-negative patients, although not for all NHL subgroups. CNS involvement occurs more frequently in patients with advanced disease.…”
Section: Discussionmentioning
confidence: 99%